Integrating natural disasters into protected area designing for global primate conservation under climate change - Li Yang; Weiying Xu; Tao Chen; Yuxuan Fan; Pengfei Fan (Geography and Sustainability)
Disaster risk reduction, an essential function of protected areas (PAs), has been generally overlooked in PA design. Using primates as a model, we designed a disaster risk index (DRI) to measure the disaster sensitivity of primate species. High-conservation-need (HCN) areas were identified by both their richness and number of threatened primate species. We also constructed high-disaster-risk (HDR) areas and climate-sensitive (CS) areas based on a disaster risk assessment and temperature change under climate change. We overlaid HCN and HDR areas to obtain HDR-HCN areas. We defined species conservation targets as the percent of each species’ range that should be effectively conserved using “Zonation”. Landslides had the highest DRI (1.43 ± 0.88), but have been overlooked in previous studies. PA coverage in HDR-HCN (30 %) areas was similar to that in HCN areas (28 %), indicating that current PA design fails to account for disaster risk reduction. About 50 % of the HDR-HCN areas overlapped with CS areas. Presently, 43 % of primate species meet their conservation targets. Fifty-seven of primate species would meet their conservation targets and 67 % of primates could benefit from PA expansion if HDR-HCN areas are fully incorporated into PAs. Increasing PA coverage in HDR-HCN areas is essential to achieving both primate conservation and disaster risk reduction. The study calls for integrating disaster risk reduction into PA design guidelines, particularly in regions like the western Amazon, and recommends flexible conservation approaches in other areas.